2018
DOI: 10.1097/md.0000000000009859
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-1-dependent pyroptosis of peripheral blood mononuclear cells predicts the development of sepsis in severe trauma patients

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 28 publications
0
46
0
Order By: Relevance
“…A published study reveals an association of NLRP3 and Caspase-1 mRNA levels with severity of sepsis caused by cytomegalovirus (CMV) [126]. Another study suggested that caspase-1 is a potential marker for predicting the development of sepsis after severe trauma [127]. These preclinical and clinical studies have revealed that the regulation of neutrophil pyroptosis may benefit in the treatment of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…A published study reveals an association of NLRP3 and Caspase-1 mRNA levels with severity of sepsis caused by cytomegalovirus (CMV) [126]. Another study suggested that caspase-1 is a potential marker for predicting the development of sepsis after severe trauma [127]. These preclinical and clinical studies have revealed that the regulation of neutrophil pyroptosis may benefit in the treatment of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Overactivated pyroptosis; however, may contribute to sepsis, septic shock, or MODS. Wang et al recently showed that an increased percentage of pyroptotic PBMCs is associated with the development of sepsis.…”
Section: Sting Signaling and Cell Deathmentioning
confidence: 99%
“…Although IL‐6 is up‐regulated in response to TLR signaling cascade, its production can be regulated directly or indirectly by CASP‐1 activation. 1 The proinflammatory cytokines IL‐6 and IL‐33 were higher in mice treated with CASP‐1 peptide inhibitor, whereas anti‐inflammatory cytokines IL‐4 and IL‐13 levels were lower 149 . In contrast, inhibition of CASP‐1 was shown to suppress the mRNA level of IL‐6, indicating that CASP‐1 acts to fine‐tune cytokine and chemokines responses to microbial stimuli 150 .…”
Section: Other Proinflammatory Cytokines and Their Roles In Pyroptosismentioning
confidence: 99%